2021
DOI: 10.3389/fnmol.2021.753936
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Injection of Kainic Acid Induces a Chronic Epileptic State in Larval Zebrafish

Abstract: Epilepsy is a common disorder of the brain characterized by spontaneous recurrent seizures, which develop gradually during a process called epileptogenesis. The mechanistic processes underlying the changes of brain tissue and networks toward increased seizure susceptibility are not fully understood. In rodents, injection of kainic acid (KA) ultimately leads to the development of spontaneous epileptic seizures, reflecting similar neuropathological characteristics as seen in patients with temporal lobe epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…It is worth mentioning that in ZF, larvae KA has been shown to be able to induce reproducibly convulsive activity also after solubilization in fish water [67], even though its behavioral effects were not detailed in the study employing this route of administration. Interestingly, in one previous study in which KA was bath applied to ZF larvae, clear convulsive seizures resembling those described in adult ZF by Alfaro et al were not observed [66], even though a much lower concentration of KA in fish water (50 µM) was able to induce electrographic activity by Kim et al in 2011 [68].…”
Section: Use Of Chemoconvulsants In Zfmentioning
confidence: 88%
See 1 more Smart Citation
“…It is worth mentioning that in ZF, larvae KA has been shown to be able to induce reproducibly convulsive activity also after solubilization in fish water [67], even though its behavioral effects were not detailed in the study employing this route of administration. Interestingly, in one previous study in which KA was bath applied to ZF larvae, clear convulsive seizures resembling those described in adult ZF by Alfaro et al were not observed [66], even though a much lower concentration of KA in fish water (50 µM) was able to induce electrographic activity by Kim et al in 2011 [68].…”
Section: Use Of Chemoconvulsants In Zfmentioning
confidence: 88%
“…In larval ZF, a recent interesting protocol consisted of infusing low KA doses in the common cardinal veins in the pericardium at 3 dpf. In the latter model, the behavioral and EEG effects of KA were well detailed as well as the antiepileptic effects of different ASD and the neurochemical effects of seizures [66]; however, this model is quite challenging from a methodological point of view. It is worth mentioning that in ZF, larvae KA has been shown to be able to induce reproducibly convulsive activity also after solubilization in fish water [67], even though its behavioral effects were not detailed in the study employing this route of administration.…”
Section: Use Of Chemoconvulsants In Zfmentioning
confidence: 99%
“…First, it is believed that the composition of gut microbiota and its metabolites and derivatives all play a role in the metabolic homeostasis of the host ( Falcinelli et al, 2015 ), but various endogenous and exogenous factors affect the composition and abundance of the microbiota and it is quite difficult to dissect well the gut microbial-host interactions ( Brugman et al, 2009 ; Roeselers et al, 2011 ; Mottaz et al, 2017 ; Yang et al, 2017 ). Second, although zebrafish are an excellent model organism that has been used to study blood diseases ( Haffter et al, 1996 ; Langenau et al, 2003 ; Dooley et al, 2008 ; van Rooijen et al, 2009 ; Taylor and Zon, 2011 ; Santoriello and Zon, 2012 ), cancer ( Amatruda et al, 2002 ; Ignatius and Langenau, 2009 ; Mione and Trede, 2010 ; Ceol et al, 2011 ; Liu and Leach, 2011 ), heart diseases ( Chen et al, 1996 ; Stainier et al, 1996 ; Poss et al, 2002 ; Poss, 2007 ; Tang et al, 2019 ; Mukherjee et al, 2021 ), muscle disorders ( Bassett and Currie, 2003 ; Follo et al, 2013 ), kidney diseases ( Tobin and Beales, 2008 ; Diep et al, 2011 ; Sander and Davidson, 2014 ; Gehrig et al, 2018 ; Brilli et al, 2019 ), central nervous system diseases ( Stewart et al, 2015 ; Heylen et al, 2021 ), and eye diseases ( Ohnesorge et al, 2019 ; Hong and Luo, 2021 ), zebrafish does have certain disadvantages in mimicking human diseases. These disadvantages include the inclusion of many gene duplications in the zebrafish genome; the phenotypic characteristics of diseases caused by direct homologous genes may differ in zebrafish and humans ( Santoriello and Zon, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Electrographic brain activity of 5 and 6 dpf larvae was assessed by non-invasive local field potential (LFP) recordings from the optic tectum as described previously ( Heylen et al, 2021 ). A blunt glass electrode (soda lime glass, Hilgenberg, Germany) pulled with DMZ Universal Puller (Zeitz, Germany) to an opening of approximately 15–20 microns, connected to a high-impedance amplifier, was filled with artificial cerebrospinal fluid (124 mM NaCl, 2 mM KCl, 2 mM MgSO 4 , 2 mM CaCl 2 , 1.25 mM KH 2 PO 4 , 26 mM NaHCO 3 and 10 mM glucose) and positioned on the skin above the optic tectum of a larva embedded in 2% low-melting point agarose (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%